Synthesis Characterization and a Physical Study of New Polyborate Compounds with Some Transitions Metal - Mohsin. E. Aldokheily (Journal of Global Pharma Technology, 2016)
This Study include preparation of polyborate compounds containing some transition metals cations  complexes which are:  [Ag (NH3)2][B5O6(OH)4].7H2O(1), [Hg(NH3)(H2O)][B5O6(OH)4]. 10H2O(2),[Hg(NH3)(H2O)][B5O6(OH)4][B3O3(OH4)].9H2O(3),[Zn(NH3)3(H2O)3][B5O6(OH)4].3H2O(4),[Zn(NH3)2(B6O7(OH)6)](5),[Zn(NH3)(H2O)5][B5O6(OH)4][B3O6(OH)4].4H2O(6),[Cd(en][B6O7(OH)6](7),[Cu(en)3][B5O6(OH)4]2.4H2O(8),[Zn2en3(B6O7(OH)6)2].3H2O(9),[Cu(1,2dmp)3] [B5O6(OH)4]2. 6H2O(10). The prepared polyborate compounds were characterized by elemental analysis (C.H.N), Infrared (FT-IR), Nuclear Magnetic Resonance Spectroscopy (1H-NMR), (13C-NMR), (11B-NMR). Some of the prepared compounds was a physically studied by measuring the molar conductivity which were used to determine thermodynamic parameters i.e the ion association constant Ka, Enthalpy ΔH 15Â°"> , Entropy ΔS 15Â°">  and Gibbs free energy ΔG 15Â°">  implenting Shedlovsky technique with matlab program. The values of Ka, ΔG 15Â°">   for pentaborate compounds were always greater than other compounds, due to the fact the pentaborate compounds more favored in ion-pair formation than other followed by hexaborate compound then the compound that containing double composition of penta and Triborates. All reactions are endothermic which were supported by the positive values of the enthalpy ΔH 15Â°.">Keywords: Pentaborate(2-), hexaborate(2-), polyborate, Shedlovsky technique.